Sistem Pendukung Keputusan Pemilihan Tempat Wisata Belanja di Kota Batam Menggunakan Metode Simple Additive Weighting (SAW) - Novitia Chinoi; Allsela Meiriza (Fakultas Teknologi Informasi Universitas Merdeka Pasuruan, 2021)
Batam city is one of the areas that are often visiting as a shopping destination by tourists because of the many attractions offered. However, the number of shopping tourism scattered is not in line with information about related tourist attractions. In addition, the number of shopping destinations often makes tourists confused in choosing shopping tourism. Therefore, the importance of a decision support system supports tourists in choose the desired shopping tourist attractions. It takes a method in its application so the desired decision support system can be achieving where one of the methods is the Simple Additive Weighting (SAW). This research uses the Simple Additive Weighting (SAW) method because it can complete multi-criteria decision-making. There are five criteria used in the selection of shopping tourism in this research, namely transportation (C1), atmosphere (C2), security (C3), product variation (C4), and facilities (C5). Based on calculations using the Simple Additive Weighting (SAW) method obtained shopping tourism attractions A4 (Alternative 4), namely Nagoya Hill, holds the highest rank value with a value of 1.00000 and makes it the most recommended shopping tourism attraction.Keywords— decision support system; DSS; shopping tour; simple additive weighting; SAW